Project-Based Learning in a high school setting: Students’ voices = tìm hiểu ý kiến của học sinh về dạy học dự án . M.A. Thesis Linguistics: 81401 - Dương, Thị Hương Giang (2019)
This is a survey research conducted at a rural upper-secondary school in Nam Dinh province. Its general objective is to evaluate the advantages and disadvantages of Project-Based Learning in the new English textbook to students in terms of the improvement in the language acquisition. Specifically, it aims to get evaluative feedback from the students about project lessons that they have experienced so that some necessary adjustments will be made and the effective elements will be explored. To achieve this purpose, a questionnaire for students was employed to collect data for the evaluation.